It’s a bear market: evolutionary and ecological effects of predation on two wild sockeye salmon populations - Lin, J E; Hard, J J; Naish, K A; Peterson, D; Hilborn, R; Hauser, L (Heredity, 2016)
Predation can affect both phenotypic variation and population productivity in the wild, but quantifying evolutionary and demographic effects of predation in natural environments is challenging. The aim of this study was to estimate selection differentials and coefficients associated with brown bear (Ursus arctos) predation in wild sockeye salmon (Oncorhynchus nerka) populations spawning in pristine habitat that is often subject to intense predation pressure. Using reconstructed genetic pedigrees, individual reproductive success (RS) was estimated in two sockeye salmon populations for two consecutive brood years with very different predation intensities across brood years. Phenotypic data on individual adult body length, body depth, stream entry timing and reproductive lifespan were used to calculate selection coefficients based on RS, and genetic variance components were estimated using animal models. Bears consistently killed larger and more recently arrived adults, although selection differentials were small. In both populations, mean RS was higher in the brood year experiencing lower predation intensity. Selection coefficients were similar across brood years with different levels of predation, often indicating stabilizing selection on reproductive lifespan as well as directional selection for longer reproductive lifespan. Despite these selection pressures, genetic covariation of morphology, phenology and lifespan appears to have maintained variation in spawner body size and stream entry timing in both populations. Our results therefore suggest considerable demographic but limited evolutionary effects of bear predation in the two study populations.